How Does Bawaslu Govern Digital Spaces Through Communication and Strategies to Address 2024 Black Campaigns? - Natasya Avania Amodya, Prabowo; Syarifa Nissa, Fauziah; Zhalika, Rahmadhania; Sajida, Sajida (Jurnal Nomosleca, 2025)
The 2024 Indonesian General Election has brought to light the central role that social media play in political narration, along with glaring instances of disinformation as well as black campaigns. These platforms are now used by political buzzers to transmit false information, which constitutes a major threat to electoral integrity. This study looks into the role of the Election Supervisory Agency (Bawaslu) in countering black campaigns and their preventive and repressive measures. The qualitative descriptive method and literature review are adopted, used to triangulate data from laws, government reports, and academic literature to test Bawaslu’s role in counteracting digital disinformation. Some preventive measures, such as public digital literacy campaigns and participatory monitoring, include initiatives like "Jaga Ruang Digital" to strengthen critical thinking and public vigilance. On the repression side are enhanced regulatory enforcement and cooperation among Kominfo and Gakkumdu in technological measures, namely the Gowaslu application for reporting by the community. The results indicate that, notwithstanding the laudable activities of Bawaslu, challenges still exist regarding regulatory loopholes, limitations in resources, and difficulty in profiling actors operating anonymously. It supports that digital regulations need to be strengthened, inter-agency collaboration needs to be pursued, and the public has to be innovatively involved in ensuring electoral integrity and accountability for democracy in the digital age.